Design of Eco Friendly Floating Restaurant for River - Eddy Setyo Koenhardono (IPTEK Journal of Proceedings Series, 2018)
Monkasel monument is one of Surabaya's landmarks and will become "The Central Business District Riverbank". In this area has been built many recreational facilities, namely the statue of Suro and Boyo, Plaza Area, BMX Area, Tribune Area, Skate Park Area and Food court Ketabang. However, the development of water tourism in this area is still not optimal. One to overcome this is the need to develop a floating restaurant that can integrate all existing facilities, especially the food court. The development of this floating restaurant has multi-function, which is increasing the visitor of the food court, because this floating restaurant only provides a place to eat not sell food, as a place of business transactions and in the long run will improve the water quality of Kalimas river. This floating restaurant is designed with high comfort and safety, and environmentally friendly, so that all the functions can be accommodated well. This is because the floating diner is a catamaran boat that has a low sweep wave and uses solar panels